Metabolomic approach in milk from calorie-restricted rats during lactation: a potential link to the programming of a healthy phenotype in offspring. - Palou, Mariona; Torrens, Juana María; Castillo, Pedro; Sánchez, Juana; Palou, Andreu; Picó, Catalina (European Journal of Nutrition, 2020)
Purpose: Mild/moderate maternal calorie restriction during lactation in rats has been associated with a lower predisposition to obesity and a healthier metabolic profile in adult offspring. Here, we aimed to assess the impact of maternal calorie restriction during lactation on milk composition to identify potential candidate components that could be involved in the programming effects in offspring. Methods: An untargeted metabolomic approach in milk samples from 20%-calorie-restricted lactating (CRL) dams and their controls was performed. Levels of leptin, adiponectin, and irisin hormones in milk were also determined at lactating days 5, 10, and 15. Results: Metabolomic analyses revealed a different metabolite pattern in milk between controls and CRL dams. 29 differential metabolites were tentatively identified (p < 0.05, FC > 1.5). Among them, myo-inositol, which showed greater levels in milk from CRL rats than controls, may be highlighted as one of the biologically plausible candidates that could be related to the beneficial effects of CRL in offspring. Results regarding myo-inositol were validated spectrophotometrically at days 10 and 15 of lactation, and levels in milk were correlated with maternal plasma levels. In addition, milk from CRL dams presented increased levels of adiponectin, decreased levels of irisin, and no changes in leptin levels vs controls throughout lactation. Conclusion: These data reveal important changes in milk composition due to calorie restriction during lactation that may be involved in the metabolic programming of the healthier phenotype of adult offspring. However, the possible contribution of the specific components is yet to be determined.